Revisiting Growth and Poverty Reduction in Indonesia: What Do Subnational Data Show? - Arsenio M. Balisacan; Ernesto M. Pernia; Abuzar Asra (Asian Development Bank (ADB), 2002)
"Indonesia has an impressive record of economic growth and poverty reduction over the past two decades. The growth-poverty nexus appears strong at the aggregate level. Newly constructed panel data on the country's 285 districts (kotamadyas/kabupatens), however, reveal huge differences in poverty changes, subnational economic growth, and local attributes. Results of econometric analysis show that besides growth, other factors directly influence the welfare of the poor, apart from their impact on growth itself. Among the critical ones are infrastructure, human capital, agricultural price incentives, and access to technology. Thus, while fostering economic growth is evidently crucial, a more complete poverty reduction strategy should take into account these relevant factors. In the context of decentralization, subnational analysis can be an instructive approach to examining local governance in relation to growth and poverty reduction."
hdl:11540/2066
Keywords: 330; Wirtschaftswachstum; Armut; Armutsbekämpfung; Indonesien